SOCIAL MEDIA MARKETING STRATEGIES FOR INDONESIAN RETAIL BUSINESSES IN DIGITAL ERA - Nida Garnida Fitrianti; Anggun Yolistina; Raden Roro Fatmasari (PT. Kreatif Indonesia Satu, 2024)
Background: Indonesian retail businesses increasingly rely on social media platforms to reach customers, yet many struggle with effective strategy implementation and measuring return on investment. Aims: This study examines successful social media marketing strategies employed by Indonesian retail businesses and identifies key performance factors that drive customer engagement and sales conversion. Research Method: Mixed-methods approach combining comprehensive surveys of 180 retail businesses across major Indonesian cities with in-depth case studies of fifteen top performers in various retail categories. Results and Conclusion: Findings reveal that consistent content posting, authentic customer engagement, platform-specific content strategies, and data-driven optimization significantly correlate with sales growth and customer retention. Instagram emerged as the most effective platform for product visualization and brand building while WhatsApp Business dominated customer service interactions and personalized marketing. Contribution: This research provides practical frameworks and actionable recommendations for Indonesian retailers to optimize their social media marketing investments, improve customer acquisition costs, and build sustainable competitive advantages in the digital marketplace.